Subliminal Adverstisement and its Effect on Consumer Purchase Intentions - Dr. Sunayana Shukla, Ms. Riya Goel (Mathematical Statistician and Engineering Applications, 2022)
The effectiveness of subliminal advertising on consumer behavior involves a lot of ambiguity and is still under scrutiny (Shaqeel Ahmad Sofi et al., 2018). On one hand there are concrete shreds of evidence researchers claiming the effectiveness of subliminal advertising on different aspects of consumer behavior; on the other hand, there are pieces of evidence which effectively manage to discard those claims (Tara Santora, 2020). The study aims to measure the difference in ‘Purchase Intentions’ of consumers after presenting subliminal stimuli via advertisements. The study adopts an experimental research design to accomplish its objectives. The participants under the experiment were young college-going students, all of them studying in a coaching academy in the district of Jharsuguda. The product under the experiment is Gold Jewellery that comes under the category of Specialty Products. Based upon previous studies, a relationship model was developed to measure the purchase intentions of the participants under the experiment. The relationship between the variables of the model was subjected to model fitness and path analysis. After qualifying through the Structural Equation Model test, the hypotheses under the experiment were statistically tested and results were reported. Paired t-test was used to find out the effect of subliminal stimuli on consumer purchase intentions. The results of the experiment revealed that there was no significant difference in the purchase intentions of the participants after being exposed to subliminal stimuli. However, there was a significant difference in ‘emotions’ and ‘perception’ of the participants after being exposed to subliminal stimuli.